Making the most of your pollinators: An epiphytic fig tree encourages its pollinators to roam between figs - Mohd Hatta, Siti Khairiyah (Ecol Evol, 2021)
Ficus species are characterized by their unusual enclosed inflorescences (figs) and their relationship with obligate pollinator fig wasps (Agaonidae). Fig trees have a variety of growth forms, but true epiphytes are rare, and one example is Ficus deltoidea of Southeast Asia. Presumably as an adaptation to epiphytism, inflorescence design in this species is exceptional, with very few flowers in female (seed‐producing) figs and unusually large seeds. Figs on male (pollinator offspring‐generating) trees have many more flowers. Many fig wasps pollinate one fig each, but because of the low number of flowers per fig, efficient utilization by F. deltoidea's pollinators depends on pollinators entering several female figs. We hypothesized that it is in the interest of the plants to allow pollinators to re‐emerge from figs on both male and female trees and that selection favors pollinator roaming because it increases their own reproductive success. Our manipulations of Blastophaga sp. pollinators in a Malaysian oil palm plantation confirmed that individual pollinators do routinely enter several figs of both sexes. Entering additional figs generated more seeds per pollinator on female trees and more pollinator offspring on male trees. Offspring sex ratios in subsequently entered figs were often less female‐biased than in the first figs they entered, which reduced their immediate value to male trees because only female offspring carry their pollen. Small numbers of large seeds in female figs of epiphytic F. deltoidea may reflect constraints on overall female fig size, because pollinator exploitation depends on mutual mimicry between male and female figs.